THE EFFECT OF SELF-EFFICACY AND EXTRINSIC REWARDS ON INNOVATIVE WORK BEHAVIOUR (IWB) MEDIATED BY WORK ENGAGEMENT ON EMPLOYEES AT PERTAMINA IN SUMBAGUT - Ramadhan, Muhammad Syahrul; Nilasari, B. Medina; Berliyanti, Dita Oki (Politeknik Negeri Ambon, 2025)
Introduction: This research aims to examine the impact of Work Engagement on Innovative Work Behaviour (IWB) among PT Pertamina employees in North Sumatra (Sumbagut), mediated by Self-Efficacy and Extrinsic Reward. To address the issues, it is essential to exhibit innovative work behaviour of the complex energy industry, including expectations for efficiency, transparent governance, and sustainable innovationMethods: This study adopts a quantitative methodology via a survey technique via a questionnaire administered to 141 Pertamina employees in Sumbagut. Data analysis was conducted via Structural Equation Modelling (SEM) through AMOS software.Results: The findings indicated that Self-Efficacy and Extrinsic Reward exert a favourable and significant influence on Innovative Work Behaviour, both directly and via the mediation of Work Engagement. This discovery validates the significance of personal self-assurance and external incentives in fostering work engagement and innovative behaviour among employees.Conclusion and suggestion: This research offers a tangible contribution to human resource management in designing strategies to improve employee innovation performance by strengthening internal and external factors and creating a work environment that supports engagement. Keywords: Self-Efficacy, Extrinsic Reward, Work Engagement, Innovative Work Behaviour.